Сyclotron wave absorption in D-shaped tokamaks - Grishanov, N.I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2016)
Transverse dielectric susceptibility elements are derived for radio-frequency waves in a large aspect ratio toroidal plasma with D-shaped magnetic surfaces by solving the Vlasov equation for untrapped and usual t-trapped particles under moderate elongation and small triangularity in the case, when the so-called d-trapped particles are absent. These dielectric characteristics are suitable for estimating the wave dissipation by the fundamental cyclotron resonance damping in the frequency range of ion-cyclotron and electron cyclotron resonances.